Maternal Dietary Patterns and Risk of Postpartum Depression: A Systematic Review. - Sun, Yuyue; Ferguson, Megan; Reeves, Marina M.; Kelly, Jaimon T. (Maternal & Child Health Journal, 2023)
Objective: Postpartum depression (PPD) has deleterious effects on both maternal and child outcomes. Poor maternal nutrition during pregnancy has been implicated in the development of PPD. This review aimed to explore the association between the overall dietary intake patterns during pregnancy and the development of PPD. Methods: A literature search was performed in PubMed, Embase, Scopus, CINAHL, and PsycINFO databases for relevant randomized controlled trials, cohort and cross-sectional studies published up to 17th September 2020. Included studies assessed at least one dietary pattern during pregnancy and reported on PPD. The Newcastle Ottawa Scale and the Joanna Briggs Institute critical appraisal tools were used to assess the quality of methodology. A narrative analysis was conducted. Results: Ten studies (eight cohort and two cross-sectional) were included with substantial heterogeneity in measurements of dietary intake exposures and PPD. The studies identified several types of healthy dietary patterns, including a 'healthy', 'health conscious', 'Japanese', 'high-glycemic index/glycemic load', 'Vegetable', 'Nut-Fruit', 'Seafood', and 'compliance with the Australian Dietary Guidelines'. The 'Western', 'unhealthy', 'Beverage', 'Cereal-Meat', and 'Egg' were labelled as unhealthy dietary patterns. Four of the eight studies showed an inverse association between adherence to healthy diets and risk of PPD, whereas only one of the seven studies showed that adherence to unhealthy diets was associated with increased risk of PPD. Methodological quality of the studies varied across the sample. Conclusions: Our findings indicate that adherence to a healthy diet may be beneficial for PPD. However, the relationship between unhealthy diets and PPD needs to be corroborated by more high-quality studies. Significance: What is already known about the topic? Nutrition has been implicated in the development, prevention and management of depression during pregnancy. Individual nutrients and foods do not consider the inter-relations of the combined exposures of the dietary components. Thus, overall dietary pattern that better represents the way pregnant women eat has been proposed to be linked with PPD. What this study adds? Healthy dietary patterns during pregnancy may be beneficial for PPD. However, the evidence suggests an inconclusive role of unhealthy dietary patterns and associations with PPD. Given the emerging evidence that supports a potential relationship between prenatal diet and maternal depressive symptoms, it is of utmost public health significance to continue research in this area.